A Comparative Eye-Tracking Study Between a Virtual Reality System and a Desktop Environment for Learning the Prepositions of Place in English. (10th February 2023) - Bacca-Acosta, Jorge; Tejada, Julian; Lampropoulos, Georgios; Avila, Cecilia
Abstract : Virtual reality (VR) is gaining momentum in language education thanks to technological advances and technology at a cost that is affordable for deploying a learning experience. However, there is a need for more research to identify the topics that are most suitable to be taught using VR in English as a foreign language (EFL) courses. In order to close part of this gap, this article reports on the results of a comparative eye-tracking study conducted with 80 university students on the effectiveness of a VR system and a desktop application for learning English prepositions of place. The results show that students using the VR system significantly outperformed those using a 2D application for learning English prepositions of place. However, students spent more time and made more mistakes in the VR system. The easiest English preposition was "on" and the most difficult one was "below" for the desktop application, and "behind" for the VR system. Some implications and recommendations for teachers are provided based on the results.